2018
DOI: 10.1002/jia2.25114
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to care, mobility and retention of HIV‐positive postpartum women in antiretroviral therapy services in South Africa

Abstract: IntroductionLinkage to care and mobility postpartum present challenges to long‐term retention after initiating antiretroviral therapy (ART) in pregnancy, but there are few insights from sub‐Saharan Africa. We aimed to describe postpartum linkage to care, mobility, retention and viral suppression after ART initiation in pregnancy.MethodsUsing routine electronic data we assessed HIV‐specific health contacts and clinic movements among women initiating ART in an integrated antenatal care (ANC) and ART clinic in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
70
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 38 publications
7
70
0
Order By: Relevance
“…While these rates are comparable with our estimate, these studies do not exclusively focus on cohorts of transferred or “down‐referred” patients who may face greater risks of disruption of care and loss to follow‐up. However, our estimate is also consistent with a study evaluating national retention in South Africa's HIV programme accounting for patient transfers estimating a 63% retention rate after six years and with a study using NHLS data to assess postpartum transfers to general ART clinics, which found 65% of women linked and in care at 24 months .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While these rates are comparable with our estimate, these studies do not exclusively focus on cohorts of transferred or “down‐referred” patients who may face greater risks of disruption of care and loss to follow‐up. However, our estimate is also consistent with a study evaluating national retention in South Africa's HIV programme accounting for patient transfers estimating a 63% retention rate after six years and with a study using NHLS data to assess postpartum transfers to general ART clinics, which found 65% of women linked and in care at 24 months .…”
Section: Discussionsupporting
confidence: 89%
“…retention rate after six years [24] and with a study using NHLS data to assess postpartum transfers to general ART clinics, which found 65% of women linked and in care at 24 months [26].…”
Section: Discussionmentioning
confidence: 99%
“…Married participants may also be responding to growing public health education on the importance of taking ART to reduce the chances of HIV transmission to uninfected partners [28]. To our knowledge, similar results have not been reported in Vietnam; however, research in China [29] and South Table 1 Unadjusted and adjusted associations between baseline characteristics and ART prescription and viral suppression among people with HIV and opioid use disorder in Vietnam, 2015-2019 (Continued) Africa [30] has shown that marriage may be positively associated with ART initiation. While depression is associated with suboptimal ART adherence [31] [32], studies are mixed on its potential association with ART initiation, with several studies demonstrating an absence of association [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 84%
“…Younger age at pregnancy, being married and attending at least two postpartum clinic visits have been cited as important for postpartum retention and viral suppression among HIV positive women in South Africa [35].…”
Section: Discussionmentioning
confidence: 99%